If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-14x+132=26(x-8)
We move all terms to the left:
-14x+132-(26(x-8))=0
We calculate terms in parentheses: -(26(x-8)), so:We get rid of parentheses
26(x-8)
We multiply parentheses
26x-208
Back to the equation:
-(26x-208)
-14x-26x+208+132=0
We add all the numbers together, and all the variables
-40x+340=0
We move all terms containing x to the left, all other terms to the right
-40x=-340
x=-340/-40
x=8+1/2
| 5.4=-t/1.5 | | 5x+10=6x+20 | | -12=0.4k | | x+24*1,5=2x-13 | | -20=0.8k | | -20=0.4k | | 19=2w−-17 | | 5^(2x−5)=74 | | 10⋅5^(2x−5)=74 | | 3,5=(1,055-x)*131,25 | | 6x+4x=4x+4 | | 13=18x+1 | | 9-4n=-9+3(9-7) | | 11=4p-2+5p=4p+8p | | 6m-10=5 | | x+(x+5)=71 | | 3x+-5x=16 | | 4(x-7)=3(91/3x) | | -v/6=-37 | | -42=-u/3 | | N-8=-4n-12 | | 12+3x=7x+10 | | x-3+x+3(x-3)=3x | | 5y=-95 | | T=7(4−3x)−8−9x+5(8x−4) | | 4x+9=7x-21 | | 28n+20=8 | | 4x+24=6x-24 | | 3x+4x+6=27 | | 3x+4x+6=27* | | (x-2)^2/4-1=0 | | 3.2+0.3x=0.2x+.4 |